Resolving the past conflict: Role of peer and supervisor support in training effectiveness - Bhatti, Muhammad Awais; Chee, Hee Hoe (Centre of Promoting Research Excellence, 2012)
Organizations, researchers and HRD professionals realized that if they want to improve the employees as well as organizational performance they have to invest in training activities. But highlighted the point whether the training is effective or not.Because if they are investing in training activities and the results are not fruitful, the investment would be considered wasting of resources.In order to make training effective, researchers and training professionals have highlighted and explained the role of different factors.Amongs different factors, researchers and training professionals have lack of consensus about peer and supervisor support. The purpose of this study is to explain the role of peer and supervisor support in training effectiveness and resolve the conflict in past studies.In order to know about the role of peer and supervisor support discussed by past researchers, different data bases, research magzines and books has been reviewed. Based on past research and training professionals views, this study suggested that in order to clearly understand the role of peer and supervisor support in training effectiveness the researchers shuold classify peer and supervisor support in three stages, pre-training, during training and post training.Finally, future research directions has been discussed.